2021
DOI: 10.1111/febs.16137
|View full text |Cite
|
Sign up to set email alerts
|

cGAS‐STING pathway: post‐translational modifications and functions in sterile inflammatory diseases

Abstract: Cytoplasmic microbial and host aberrant DNAs act as danger signals and trigger host immune responses. Upon recognition, the cytosolic DNA sensor cyclic GMP–AMP synthase (cGAS) catalyzes the production of a second messenger 2′3′‐cGAMP, which activates endoplasmic reticulum (ER)‐associated stimulator of interferon (IFN) genes (STING) and ultimately leads to the induction of type I IFNs and inflammatory genes that collectively initiate host immune defense against microbial invasion. Inappropriate activation or su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 188 publications
0
20
0
Order By: Relevance
“…After activation, STING trafficked to Golgi, in which the post-translational modification (PTMs) occurs for recruiting and activating TBK1. The activation, protein localization, and protein–protein interactions of STING are also regulated by several PTM processes, including ubiquitylation, SUMOylation, phosphorylation, and palmitoylation [ 52 , 53 ]. The data from this result assume that the Western blot from cell lysate showed another upper band of STING after the DMXAA activation could be due to the several PTMs processes.…”
Section: Discussionmentioning
confidence: 99%
“…After activation, STING trafficked to Golgi, in which the post-translational modification (PTMs) occurs for recruiting and activating TBK1. The activation, protein localization, and protein–protein interactions of STING are also regulated by several PTM processes, including ubiquitylation, SUMOylation, phosphorylation, and palmitoylation [ 52 , 53 ]. The data from this result assume that the Western blot from cell lysate showed another upper band of STING after the DMXAA activation could be due to the several PTMs processes.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that viruses benefit from hijacking host enzymes to alter the modification of antiviral immune cascades component proteins, thus conducive to their replication ( Carty et al, 2021 ; Hong et al, 2021 ; Song et al, 2021 ). Understanding the details of PTMs in cGAS-STING signaling helps interrupt virus evasion.…”
Section: Post-translational Modification Of Cyclic Gmp-amp Synthase-stimulator Of Interferon Genes Pathway Components Is Significant To Amentioning
confidence: 99%
“…STING, the adaptor downstream of cGAS, is also the center molecule of most DNA-sensing pathways. Multiple PTMs have been found to dominate STING intracellular trafficking, conformational change, and activation during infection ( Li et al, 2020 ; Hong et al, 2021 ). One of the most common modifications that dynamically regulates STING activity is ubiquitination.…”
Section: Post-translational Modification Of Cyclic Gmp-amp Synthase-stimulator Of Interferon Genes Pathway Components Is Significant To Amentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, cGAS has a wide cellular distribution that involves localization at the inner leaflet of the plasma membrane, cytoplasm, and nucleus ( Sun et al., 2013 ; Barnett et al., 2019 ; Jiang et al., 2019 ). Multifaceted safeguard mechanisms have been adopted by the host to prevent aberrant cGAS‒STING signaling-induced autoreactivity under steady-state conditions, which include (i) segregation of cGAS away from extracellular DNA and mtDNA via compartmentalization of cGAS to the cytosol and the inner plasma membrane, (ii) tight tethering of nuclear cGAS by histones to prevent cGAS activation by genomic DNA ( Boyer et al., 2020 ; Kujirai et al., 2020 ; Michalski et al., 2020 ; Pathare et al., 2020 ; Zhao et al., 2020a ), (iii) nucleases and phosphodiesterases that degrade immunogenic DNA and 2′3′-cGAMP ( Li et al., 2014 ; Motwani et al., 2019b ), and (iv) sophisticated protein‒protein interaction and posttranslational modification (PTM) networks to maintain the stability and functionality of cGAS and STING ( Hertzog and Rehwinkel, 2020 ; Hong et al., 2021a ). Disrupting one piece of these regulatory mechanisms leads to the imbalance of cGAS‒STING signaling that induces or aggregates multiple sterile inflammatory diseases, including autoimmune diseases, neurodegenerative diseases, metabolic disorders, and cancers ( Bai and Liu, 2019 ; Motwani et al., 2019b ; Paul et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%